ISOLATION AND ANTI FUNGAL SUSCEPTIBILITIES OF PHYTOPATHOGENIC FUNGI FROM INFECTED YAM LEAVES IN ZARIA, NIGERIA - Jodi, S. M.; Ehinmidu, J. O. (FUDMA JOURNAL OF SCIENCES, 2021)
In order to study the disease causing organisms that reduces the quantity and quality of yam produced, which makes them unappealing to consumers, isolation of phytopathogenic fungi from infected yam leaves in the field at Zaria was carried out. The phytopathogenic infected yam leaves were surface sterilized with 70% alcohol, swabbed aseptically with sterile cotton swab stick and then inoculated on sterile Sabourand dextrose agar (SDA) suplimented with 0.1% of penicillin and streptomycin. The inoculated plates were incubated at 300C for 5 days. The growth were isolated in pure culture, and then characterized fully. The fourteen fungal species identified namely Aspergillus niger, Cladosporium sp, Aspergillus ostianus, Scopolarium sp, Aspergillus flavus, Rhizopus sp, Penicillium citrinum, Aspergillus wentii, Penicillium oxalicum, Aspergillus cervinus, Penicillium sp, Aspergillus fumigatus, Aspergillus oryzae and Rhizopus stolonifer were subjected to different concentrations of the following antifungal agents: Terbinafine HCl; Fluconazole; Flucytosine; Benomyl and Sodium propionate. The susceptibilities (MICs and MFCs), the percentage of occurrence of the 14 identified isolates and their distribution in 12 farms and three towns studied were also determine.